Bronchiectasis in patients with chronic obstructive pulmonary disease (Journal of Pathology of Nepal, 2018)
Background: Chronic obstructive pulmonary disease is most common disease entity and third leading cause of mortality worldwide. The presence of bronchiectasis in severe chronic obstructive pulmonary disease patients had led to frequent exacerbation requiring hospitalizations. The purpose of this study was to identify the factors associated with bronchiectasis, using routine data collected during medical visits from patients diagnosed with chronic obstructive pulmonary disease.Materials and Methods: This is hospital based cross sectional study conducted on 120 chronic obstructive pulmonary disease patients. All patients were subjected through history, examination, pulmonary function test, sputum samples and imaging of chest.Results: Out of 120 patients among them 67 patients (55.8%) were chronic obstructive pulmonary disease without bronchiectasis while 53 patients (44.1%) had chronic obstructive pulmonary disease with bronchiectasis. Thirty patients (56.6%) having chronic obstructive pulmonary disease with bronchiectasis and 18 patient (26.8%) having chronic obstructive pulmonary disease without bronchiectasis had exacerbation in one year requiring hospitalisation. Most common organisms isolated were Pseudomonas Aeruginosa in 20 patients (55.5%), Klebsillae Pneumoniae in 6 patients (16.6%) among chronic obstructive pulmonary disease with bronchiectasis group.Conclusion: Chronic obstructive pulmonary disease patient with severe airflow limitation, with frequent exacerbation and colonisation with isolation of organisms resulting in bronchiectasis requiring frequent hospitalisation.